Functions of biogenic magnetic nanoparticles in organisms - Gorobets, S.V.; Gorobets, O.Yu. (Functional Materials, 2012)
The functions of the biogenic magnetic nanoparticles both in bacteria and multicellular organisms arc studied in this paper using methods of bioinformatics and the modeling experiments in the field of magnetochemistry. Thus it was revealed that biogenic magnetic nanoparticles arc necessary not only for the navigation in a magnetic field of the Earth but for accumulation of paramagnetic species such as Fe ions and oxygen and for regulation of transport processes in a cell by changing concentration gradients of different species according to their magnetic susceptibility. The similarity between the genes of magnetosome island of magnetotactic bacteria and human genes have been studied by means of bioinformatics methods for prediction of functions and physiological origin of biogenic magnetic nanoparticles in multicellular organisms. As a result, it was revealed that human proteins (which arc the homologues with the proteins of magnetosome island) have been implicated in pathogenesis of a number of diseases, characterized by the elevated level of biogenic magnetic nanoparticles.